Livestock Insurance Prospects in the Republic of Armenia - Nersisyan, Nerses («Տնտեսագետ» հրատ․)
The article analyzes the indicators, changes, and existing opportunities for the introduction and development of insurance products in one of the most important branches of RA agriculture - livestock breeding. There are many types of insurance worldwide, which are gradually gaining life and gaining importance in the Republic of Armenia. For example, recently, the product "job loss insurance" of "Ingo Armenia" Insurance Company has received great resonance (banks news). Such products, of course, are both interesting and surprising, as they reflect the aspirations of the insurance market development and characterize the market formation in our country. But still, are these types of products even more important than, for example, beekeeping insurance? Will the development of these products lead to faster economic development than the advancement of agri-insurance? Looking at the "huge investment" of agriculture among the industries contributing to economic growth, at least at the state level, the development of agri-insurance types cannot be ignored. It is for these and many other reasons that this paper presents the development and prospects of one of the most developed branches of the agricultural sector - livestock insurance in our country. Livestock insurance is a beneficial product for farmers against the loss or damage of animals, which provides financial protection in case of certain risks. Livestock insurance, like other types of insurance, covers certain risks, particularly the loss of animals due to accidents, diseases, or other types of natural disasters such as earthquakes, landslides, fires, etc. However, it should be noted that the volatility of agricultural production, especially in the livestock sector, and the high dependence of performance on a large number of accidents lead to the fact that the level of insurance risk and, consequently, the volume of agricultural risk insurance rates are very high.
Keywords: Finance